2018
DOI: 10.1371/journal.pone.0200014
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA missense mutations promote glioblastoma pathogenesis, but do not enhance targeted PI3K inhibition

Abstract: BackgroundGlioblastoma (GBM) is the most common adult primary brain tumor. Multimodal treatment is empiric and prognosis remains poor. Recurrent PIK3CA missense mutations (PIK3CAmut) in GBM are restricted to three functional domains: adaptor binding (ABD), helical, and kinase. Defining how these mutations influence gliomagenesis and response to kinase inhibitors may aid in the clinical development of novel targeted therapies in biomarker-stratified patients.MethodsWe used normal human astrocytes immortalized v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
(94 reference statements)
2
14
0
Order By: Relevance
“…It has been suggested that glioblastoma cell lines with helical domain mutations are still sensitive to dual PI3Ki/MEKi treatment [9], which is consistent with our observation that the EGFR-signaling pathway is adjustable in cell line SF767. Also, it has been found that Gefitinib inhibited EGFR phosphorylation in U251MG and SF767 cells, whereas Gefitinib inhibited AKT phosphorylation only in SF767 cells but not in U251MG cells [18], consistent to Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been suggested that glioblastoma cell lines with helical domain mutations are still sensitive to dual PI3Ki/MEKi treatment [9], which is consistent with our observation that the EGFR-signaling pathway is adjustable in cell line SF767. Also, it has been found that Gefitinib inhibited EGFR phosphorylation in U251MG and SF767 cells, whereas Gefitinib inhibited AKT phosphorylation only in SF767 cells but not in U251MG cells [18], consistent to Fig.…”
Section: Discussionsupporting
confidence: 92%
“…A meaningful analysis of the EGFR-signaling pathway is possible only in a cell line with an adjustable pathway, e.g., by a response to ligand stimulation or treatment by a tyrosine kinase inhibitor (TKI) [9]. Hence, we investigated four glioblastoma cell lines in a pilot study to identify a cell line with an adjustable EGFR-signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al demonstrated that PTEN mutations are associated with therapeutic resistance [31]; while Benitez et al demonstrated that PTEN regulates GBM oncogenesis [32]. Mutations in the PIK3R1gene have been shown to promote the growth and formation of gliomas [33], while PIK3CA missense mutations have been shown to promote GBM pathogenesis [34].…”
Section: Selection Of Mutated Genes For Personalisationmentioning
confidence: 99%
“…Only GBM 5 contained variants of the PIK3CA gene (Figure 2). Missense mutations in this gene have been shown to make GBMs more sensitive to treatment with a combination containing a phosphoinositide 3-kinase (P3K) inhibitor and a mitogen-activated protein kinase (MEK) inhibitor [34]. CEL has been shown to be both a P3K and MEK inhibitor [50,51], thus removing it from the combination reduced the combinations efficacy against GBM 5 ( Figure 3B).…”
Section: The Influence Of Personalisation On Cell Viabilitymentioning
confidence: 99%
“…The PI3K pathway is also activated by gain-of-function mutations in the PI3K catalytic subunit gene (PIK3CA). These mutations occur in up to 10% of GBMs and result in constitutive activation of the pathway with downstream effects similar to those promoted by EGFRvIII and PTEN mutations [81]. The key role of PI3K-Akt pathway in oncogenesis has sparked increasing interest in using small molecular inhibitors to target this pathway.…”
Section: The Molecular Hallmarks Of Invasion In Gbmmentioning
confidence: 99%